The Role of Neoadjuvant Chemoradiation Therapy in Patients With Borderline Resectable Pancreatic Cancer With Isolated Venous Vascular Involvement. Issue 31 (August 2015) - Lee, Jin Ho; Kang, Chang Moo; Bang, Seung Min; Choi, Jin Young; Seong, Jin Sil; Hwang, Ho Kyoung; Choi, Sung Hoon; Lee, Woo Jung; Wenfu, Tang.
<x xml:space="preserve">Abstract</x> Abstract The rationale for neoadjuvant chemoradiation therapy (Neo-CRT) and the definition of borderline resectable pancreatic cancer (BRPC) are still controversial. In particular, surgical treatment of BRPC with isolated venous vascular involvement (IVVI) is debatable. From January 2000 to December 2013, 84 patients diagnosed with BRPC according to NCCN guidelines were identified, and 70 patients were found to have BRPC with IVVI. We divided all 70 patients into 3 groups: surgery first without Neo-CRT (Group 1); pancreatectomy following Neo-CRT (Group 2); and no operation following Neo-CRT (Group 3). Patient characteristics including oncologic outcomes were analyzed for each of the 3 patients groups. Thirty-seven patients were female and 33 were male, with a mean age of 61.7 ± 9.74 years. Among the 70 BRPC patients with IVVI, 28 patients (40%) belonged to Group 1, 30 patients (42.9%) belonged to Group 2, and 12 patients (17.1%) belonged to Group 3. Pathological tumor size (P < 0.001), pT stage (P = 0.001), pTNM stage (P = 0.002), combined vascular resection (P = 0.003), completeness of adjuvant therapy (P = 0.004) were found to be statistically significantly different between Groups 1 and 2. In addition, disease-free survival (P = 0.055) and disease-specific survival (DSS) (P = 0.006) were improved in Group 2. Interestingly, when comparing DSS, there was no statistically significant difference between Groups 1 and 3 (P = 0.991). The clinical practice of pancreatectomy following Neo-CRT in BRPC with IVVI provided favorable oncologic outcomes. The effect of Neo-CRT in BRPC with IVVI may be multifactorial, providing proper patient selection, complete adjuvant chemotherapy, and potential therapeutic (downstaging) effect.